Women's invisible work in disaster contexts: Gender norms in speech on women's work after a forest fire in Sweden - Danielsson, Erna; Eriksson, Kerstin (Disasters, 2022)
The aim of this study is to investigate what women do in disaster situations and how both men and women perceive and discuss the work of women. These patterns were evidenced in the stories that were told following the largest forest fire in the modern history of Sweden in July 2014. The study is based on 31 retrospective interviews with volunteers involved in combating the forest fire and concentrates on stories about the supportive work of women during this disaster. The results indicate that women were praised when they followed traditional norms but were denigrated when they performed what were viewed as male-coded tasks. The stories reveal norms concerning what a woman is and is not by focusing on women's age and clothing and by directly and indirectly questioning their abilities and authority. The norms are also rendered visible by the positive attention that women receive while describing doing what is expected of them
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; catastrophe naturelle; division sexuelle du travail; environnement; europe; normes de genre; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; stéréotypes de genre; suède; thématiques; travail

L'improvisation jazz : une pratique fondamentale dans le processus de reconnaissance des musiciennes de Montréal - Champagne, Lysandre (Université du Québec à Montréal, 2019)
À partir des dimensions spatiale, temporelle et musicale, ce mémoire expose les modalités de reconnaissance des improvisatrices de jazz dans les jam-sessions de Montréal. En se référant au concept de Jeu chez Mead, l'autrice montre que l'authentification des musiciennes en situation d'improvisation est le produit de la communication mise en forme par ce type d'interaction. Toutefois, le contexte des jam-sessions montréalais maintient un «entre-soi» masculin défavorable à la reconnaissance des musiciennes comme improvisatrices distinctes dans ce jeu musical. Ainsi, l'improvisation dans ces événements de jazz participe à la reconduction des inégalités de genre.
https://uqam-bib.on.worldcat.org/oclc/1110591322
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; discipline; environnement; femmes* artistes; femmes* musiciennes; genre; montréal; mémoires/thèses; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; étude qualitative

Combattre maintenant les inégalités sexuées, sociales et territoriales dans les quartiers politique de la ville et dans les territoires ruraux fragilisés - Haut Conseil à l'Égalité entre les femmes et les hommes (2014)
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discipline; environnement; europe; france; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; systèmes d'oppressions; thématiques; travail; urbanisme